The facets model of effects and Islam in integrated marketing communication: the case of Gubugklakah in Indonesia - Nadia, Zulfa; Mokhtar, Aida (2015)
This study examined the integrated marketing communication (IMC) campaign of a tourism village (Desa Wisata) named Gubugklakah (later DWG) in Malang, Eastern Java, Indonesia. In 2010, a group of students from Gadjah Mada University had the idea of turning Gubugklakah into a tourism village because of its natural resources and strategic location as it is on the alternative path to the active volcano, mount Bromo. The village was promoted by way of the Kuliah Kerja Nyata (KKN) program that is a three-year project that works by sending out a group of 30 students from various departments each year for about one and a half months there to mingle, work in teams with the local youth, and promote the village as a tourism village. In 2012, the main project by the students was complete but the villagers continued with the tourism campaign on their own. In only two years until 2014, they successfully obtained a turnover of 500 million rupiah each month as there was an increasing demand from tourists to visit their village. Before that, most of the villagers worked as farmers and they did not make any profit from their natural resources other than farming. In view of this, the newly established Gubugklakah is chosen for this qualitative case study, by examining how an IMC campaign had effectively been conducted to promote the village to be successful in just a few years guided by the facets model of effects. With the growing number of Muslim travelers globally, the importance of Islamic tourism that is travelling 343 which is not contrary with Islamic law in terms of being harmful to tourists and the larger society (Laderlah, Rahman, Awang, & Man, 2011) in this case study is apparent. This study also examined DWG from the Islamic perspective. The findings suggest that four marketing communication tools were used in accordance with the six facets model of effects: perception, affective, cognition, association, persuasion and behaviour and that DWG is a Muslim friendly tourism village. This study contributes to current knowledge by bridging the gap between theory and practice and by examining a successful IMC campaign using the facets model of effects and from the Islamic perspective.